The evolution of Patinkin's interpretation of Keynes' principle of effective demand. Issue 3 (4th May 2022) - Hartwig, Jochen
Abstract: Don Patinkin (1922–1995) was both an eminent theoretical economist and a great historian of economic thought. In the latter field, his focus was on Keynes' "principle of effective demand" from Chapter 3 of the General Theory . Having submitted a first interpretation of the "principle" in 1976 – in which he claimed that it contains major flaws – Patinkin revisited the subject several times over the next couple of years. In this process, his interpretation changed markedly. The aim of this paper is to trace (and to comment on) the evolution of Patinkin's interpretation of the theory of effective demand.